Antimicrobial susceptibility of Leptospira spp. isolated from environmental, human and animal sources in Malaysia - Benacer, Douadi; Mohd Zain, Siti Nursheena; Peck, Toung Ooi; Kwai, Lin Thong (Medknow Publications, 2017)
Leptospirosis is a zoonosis with worldwide distribution caused by pathogenic spirochetes of the genus Leptospira. The aim of this study was to evaluate the susceptibility of isolates obtained from different hosts. A total of 65 Leptospira isolates from humans (n = 1), zoonoses (rat, n = 60; dog, n = 1; swine, n = 1) and environment (n = 2) were tested against six antibiotics. All the isolates were resistant to trimethoprim and sulphamethoxazole and had high MIC toward chloramphenicol (MIC90: 6.25 μg/ml). All except one environment isolate were sensitive to ampicillin, doxycycline and penicillin G.